Diversidade cariotípica e molecular de Leptodactylus (Anura, Leptodactylidae) e obtenção de sondas cromossomo-específicas de anfíbio por citometria de fluxo - Gazoni, Thiago [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The genus Leptodactylus currently has 74 recognized species in the Neotropical Region, of which 57 were reported in Brazil. Factors such as high morphological similarity, as well as the lack of diverse data from different populations, result in the confusing taxonomic status of some species in the genus. Advances in this matter were obtained by increasing studies involving mainly comparison of molecular data, but often are not examined specimens collected in the type localities, fundamental for assessing the real diversity of species, considered underestimated for amphibians in general. Besides the importance of cytogenetics in describing the genomic organization, such as the presence of chromosomal sex determination systems, different cytogenetic data has been an important tool for studying frogs, allowing comparison of chromosomal variations, inferring / identifying through these the suggestion of taxa, especially when combined with zoological and ecological information. Here we studied cytogenetically species currently in the genus Leptodactylus. Among the results are outstanding: the identification of an extraordinary chromosome system of sex determining in L. pentadactylus (X1X2X3X4X5X6: Y1Y2Y3Y4Y5Y6), considered the highest reported for vertebrates; Cytogenetic and molecular review of specimens in the Leptodactylus melanonotus group, which are in a complex of species pending resolution. With our data, it was possible revalidate the species L. brevipes and L. intermedius as they were in synonymy with L. petersii. Additionally we showed the first construction of DNA probes from whole chromosomes of amphibian, obtained by flow cytometry from Xenopus tropicalis, a model organism for genetic and developmental studies, and the possibility of application in the studies on chromosome evolution of other species of frogs, even those phylogenetically ...

O gênero Leptodactylus compreende, atualmente, 74 espécies distribuídas na Região Neotropical, das quais 57 foram relatadas no Brasil. Fatores como a alta similaridade morfológica, bem como a carência de dados diversificados de diferentes populações, refletem no status taxonômico confuso para alguns dos representantes do gênero. Avanços nessa questão foram obtidos através do aumento de estudos, principalmente aqueles envolvendo comparação de dados moleculares mas, muitas vezes, não foram analisados espécimes coletados em localidade tipo, fundamental para a avaliação da real diversidade de espécies, considerada subestimada para os anfíbios anuros em geral. Além da importância da citogenética em diferentes aspectos referentes à organização genômica, bem como na identificação de sistemas de determinação cromossômica do sexo, diferentes dados citogenéticos têm se mostrado uma importante ferramenta para o estudo de anuros, permitindo, pela comparação das variações cromossômicas, a identificação de espécies crípticas, principalmente quando aliados a informações moleculares, zoológicas e ecológicas. Entre os objetivos do presente trabalho destacam-se a busca por variações cariotípicas que auxiliem na elucidação de problemas de taxonomia e sistemática no gênero Leptodactylus, pelo emprego de técnicas de citogenética clássica e molecular, bem como a obtenção de sondas cromossomo-específicas para procedimentos de pintura cromossômica em anfíbios anuros. Entre os resultados obtidos, são destacados: a identificação de um extraordinário sistema cromossômico de determinação do sexo em L. pentadactylus (X1X2X3X4X5X6:Y1Y2Y3Y4Y5Y6), considerado o maior já relatado para vertebrados; a revisão citogenética e molecular de espécimes do grupo de L. melanonotus, o qual apresenta complexo de espécies pendente de resolução. Os dados obtidos indicam a revalidação das espécies L. brevipes e L....
Keywords: Anura; Anuro; Citogenetica; Genetica animal; Cromossomos sexuais; Cariotipos